Asimtotik Model Multivariate Adaptive Regression Spline - Otok, Bambang Widjanarko; Guritno, Suryo; Subanar, Subanar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Parameter estimation in MARS model executed by minimizing penalized least-squarer (PLS). Through somerequirement, asymtotic estimator characteristic from MARS prediction model has been successfully proven. Theresearch result shows that GCV can work properly to determine the best model that applied on MARS model. Solar’s vehicles produce opacity that exceed the standard limit of emition quality which was adjusted in Kepmen LH No.35 Year 1993, as large as 88 percent from 408 percent. Applying years, cylinder volume, type of machine, andvehicle’s radius are the variables that influences the opacity.